Pengaruh Media Kartu Kata Rumpang Bergambar dan Minat Baca Terhadap Pemahaman Bacaan Siswa Kelas II Sekolah Dasar - Ni'mah, Amelia Zahrotun; , Sukartono (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The low interest in reading students that is happening now coupled with the application of boring learning causes a lack of students' understanding of a reading comprehension in Indonesian language material. This study has objectives including: 1) determining the influence of picture missing word card media on students' reading comprehension; 2) knowing the influence of reading interest on students' reading comprehension; 3) Knowing the mutual influence between picture missing word card media and students' reading interest in students' reading comprehension. This study uses a type of quantitative research with ex post facto methods. The process of collecting data is carried out by documentation techniques and questionnaires. The study sample consisted of 52 students. Such instruments are tested with validity and reliability. Normality testing (Kolmogorov Smirnov) and linearity testing were carried out as research prerequisite tests. In addition, the t test is used as a simple linear regression hypothesis test, while the F test is used for multiple regression tests. This study states: 1) There is an influence of picture clump word card media on reading comprehension as evidenced by the acquisition of tcount = 3.626 > ttable = 2.008. 2) There is an influence of reading interest on reading comprehension. This is based on the acquisition tcount = 3.314 > ttable = 2.008. 3) There is a simultaneous influence between the medium of picture sticky word cards and reading interest on students' reading comprehension. It is based on the values Fcount = 10.014 > Ftable = 3.19.